2023
DOI: 10.3390/antibiotics12071117
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Colistin Resistance (mcr) Gene-Containing Organisms in Poultry Sector in Low- and Middle-Income Countries: Epidemiology, Characteristics, and One Health Control Strategies

Abstract: Mobile colistin resistance (mcr) genes (mcr-1 to mcr-10) are plasmid-encoded genes that threaten the clinical utility of colistin (COL), one of the highest-priority critically important antibiotics (HP-CIAs) used to treat infections caused by multidrug-resistant and extensively drug-resistant bacteria in humans and animals. For more than six decades, COL has been used largely unregulated in the poultry sector in low- and middle-income countries (LMICs), and this has led to the development/spread of mcr gene-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 299 publications
0
3
0
Order By: Relevance
“…In 2018, colistin presented only 0,1% of Escherichia coli as resistant and in 2020 this number rose to 1,5%. These values are of great concern to the scientific community and several studies have recently been carried out to fully understand the resistance mechanisms associated with this namely plasmids and chromosomal mediation [48,49]. A very positive highlight is the fact that none of the antibiotics tested in 2022 show 100% resistance, with the highest resistance value belonging to Amoxicillin/Clavulanic Acid.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, colistin presented only 0,1% of Escherichia coli as resistant and in 2020 this number rose to 1,5%. These values are of great concern to the scientific community and several studies have recently been carried out to fully understand the resistance mechanisms associated with this namely plasmids and chromosomal mediation [48,49]. A very positive highlight is the fact that none of the antibiotics tested in 2022 show 100% resistance, with the highest resistance value belonging to Amoxicillin/Clavulanic Acid.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of 10 different classes of mcr , all of which encode pEtN transferases. Subsequent research showed that mcr-1 is distributed globally in a variety of different Enterobacteriaceae, but mainly E. coli ( Anyanwu et al., 2023 ).…”
Section: Colistin Resistancementioning
confidence: 99%
“…Of concern is the increasing prevalence of multidrug resistant Salmonella species associated with higher morbidity in humans [ 28 , 31 ], including resistance to amphenicols, sulphonamides, carbapenems, macrolides, and tetracycline [ 28 , 32 , 33 ]. Studies attribute this to previous exposure to antimicrobials and a history of international travel [ 27 , 31 , 34 , 35 ]. For example, international travel has been identified as a risk factor for acquiring extended-spectrum beta-lactamases-producing Enterobacteriaceae [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%